Incomplete peripheral retinal vascularisation in retinopathy of prematurity: is it the consequence of changing oxygen saturation? - Yehiam, Sigal Zmujack; Simkin, Samantha K.; Al-Taie, Rasha; Wong, Maisie; Battin, Malcolm; Dai, Shuan (Frontiers in Pediatrics, 2023)
Background We wish to determine the prevalence and risk factors of incomplete peripheral avascular retina (IPAR) in children screened for retinopathy of prematurity (ROP) and its association with oxygen saturation (SpO2) targets. Methods A retrospective review of retinal images of premature infants born and screened for ROP in Auckland Region, New Zealand, between January 2013 and December 2017 was conducted. Images were reviewed to determine if avascular retina was present at their final ROP screening. The prevalence of peripheral avascular retina was compared among infants born prior to (Group 1) and after (Group 2) 2015 when the SpO2 target was increased. Infants with any concurrent ocular pathology or who had received ROP treatment were excluded. Results In total, 62 (12.8%) of the total of 486 infants (247 in Group 1; 239 in Group 2) were found to have IPAR at their last ROP screening. Group 1 had more statistically significant infants with IPAR compared to Group 2 (39/247 infants and 23/239 infants respectively; p = 0.043). Conclusions Incomplete peripheral retinal vascularisation occurred at a prevalence of 12.8% in infants at risk of ROP. Higher SpO2 targets did not increase the prevalence of incomplete peripheral retinal vascularisation. Low gestational age and low birth weight are likely risk factors for the development of avascular retina. Further research into the risk factors associated with incomplete peripheral retinal vascularisation and the associated long-term outcomes is needed.